Prawny status zawodu lekarza. Wybrane zagadnienia - Kosiński, Eryk (Studia Prawa Publicznego, 2019)
The article deals with a very crucial question of the legal status of physicians in Poland. The question asked is whether a physician who works as a sole practitioner may be recognized as a person performing a liberal profession, a public trust profession (a category speciﬁ c only as far as Polish domestic law concerned), or a regulated profession (according to Directive 2005/36/EC of the European Parliament and of the Council of 7 September 2005 on the recognition of professional qualiﬁ cations). Consequently, ﬁrst the concepts of a liberal, regulated and public trust professions are analysed. Another important question to be answered is if physicians practicing as sole traders are undertakings in the meaning of the EU law and if they are what their status is. The vastest exclusion in terms of the subject and object of the legislation was provided by the Regulation on Industrial Law issued by Poland’s President on 7 June 1927 which excluded the activity conducted by physicians. Under Article 3 of the President’s Regulation the Commercial Code 27 June 1934, all liberal professions were also excluded from activities considered to be a form of entrepreneurship. This attitude changed in postwar Poland and the Act of 23 December 1988 on Economic Activity provided for no exclusion for any liberal profession from being regarded as economic activity. The Act of 19 November 1999 on Economic Activity excluded from its scope only entities that provided legal services (barristers and solicitors) and those rendering services in the area of industrial property. Today, under Polish law physicians are considered to be an undertaking in two situations: when they conduct their activities in the form of so-called ‘private practice’ (one-person undertaking), or when they conduct their practice within so-called ‘collective practice’ (partnership). They are not regarded as undertakings when they are employed by a medical institution or another medical entity on the basis of an employment contract. In such a case they fall under the provisions of the Act of 15 April 2011 on Medical Activities, but still keep the status of liberal profession.